The Influence of Financial Literacy, E-Money, Consumptive Lifestyle and Financial Distress on Gen Z's Personal Financial Management Behavior with Mental Accounting as a Moderation Variable - Enggar Nursasi; Risma Handayani Istiqomah; Benita Rahmania (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
This study investigates the influence of financial literacy, e-money usage, consumptive lifestyle, and financial distress on financial management behavior, with mental accounting as a moderating variable. The research was motivated by the growing challenges faced by individuals in managing personal finances amidst digitalization and increased consumption patterns. Using a quantitative approach, data were collected through surveys and analyzed with Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results reveal that financial literacy, e-money, and consumptive lifestyle have a significant positive effect on financial management behavior, while financial distress shows no significant influence. Furthermore, mental accounting strengthens the effect of financial literacy on financial management, indicating its crucial role in shaping rational decision-making. These findings highlight the importance of improving financial knowledge and self-regulation in the digital economy era. The study provides both theoretical contributions and practical implications for enhancing financial behavior